Implementation of Mujahadah and Syaja'ah Personal Morals in the Perspective of Islamic Education - Reni Sasmita; Waharjani (Journal of Islamic Civilization, 2022)
This research aims to examine and describe how students practice mujahadah and syaja'ah morals. The method used in this study is a qualitative method with a library approach. The morals of mujahadah and syaja'ah need to be instilled in a Muslim. By having the behavior of mujahadah and syaja'ah, Muslims will have the fighting spirit (to be serious) and the courage to carry out all good deeds, both in being severe in fighting lust, doing Amar ma'ruf, and leaving nahi mungkar. They will also have courage in defending the truth, separating the rights from vanity, and fighting against the passions and jihad in the way of Allah. As for implementing mujahadah and syaja'ah morals in oneself, children have a strong determination (determination) in studying and carrying out worship and avoiding prohibitions, the courage to express their opinions in public, and the courage to fight evil that occurs around them. As a result, people with mujahadah and syaja'ah morals are also optimistic, patient, responsible, never giving up, trusting, and sincere. Tujuan dari penelitian ini adalah untuk menganalisis dan memaparkan implementasi akhlak mujahadah dan syaja’ah dalam diri peserta didik. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan kepustakaan. Akhlak mujahadah dan syaja’ah perlu untuk ditanamkan dalam diri seorang muslim. Dengan memiliki perilaku mujahadah dan syaja’ah maka umat Islam akan memiliki daya juang (bersungguh-sungguh ) dan memiliki keberanian dalam melaksanakan segala amalan-amalan kebaikan, baik  dalam bersungguh-sungguh dalam melawan hawa nafsu, mengerjakan amar ma’ruf dan meninggalkan nahi mungkar, memiliki kebranian dalam membela kebenaran, memisahkan yang hak an batil dan keberanian dalam berperang melawan hawa nafsu dan berjihad di jalan Allah. Adapun implementasi dari akhlak mujahadah dan syaja’ah dalam diri adalah anak memiliki kesungguhan (tekat) yang kuat dalam menuntut ilmu maupun melaksanakan ibadah-ibadah dan menjauhi larangannya, memiliki keberanian dalam mengungkapkan keberanian dan berpendapat di depan umum, dan berani dalam melawan kemungkaran yang terjadi di sekitarnya. Sehingga orang yang memiliki akhlak mujahadah dan syaja’ah juga memiliki optimis yang tinggi, sabar, bertanggung jawab, pantang menyerah, tawakal dan ikhlas.